Genetic association between circulating selenium level and the risk of schizophrenia in the European population: A two-sample Mendelian randomization study - Deng, Ming-Gang; Cui, Han-Tao; Nie, Jia-Qi; Liang, Yuehui; Chai, Chen (Frontiers in Nutrition, 2022)
Background: The causal association between circulating selenium level and the risk of schizophrenia remains unclear. Objective: To determine the causal relationship between circulating selenium level and the risk of schizophrenia, using the Mendelian Randomization method in the European population. Methods: Single nucleotide polymorphisms (SNPs) associated with circulating selenium level were identified at p<5×10-8. The inverse variance weighted (IVW) method was used as the principal MR analysis, and MR Egger, weighted median, and MR PRESSO were used to determine the accuracy of IVW results. Cochran’s Q test and Leave-One-Out sensitivity analysis were performed to evaluate the heterogeneity and stability of genetic variants on schizophrenia. Results: Circulating selenium level was associated with decreased risk of schizophrenia by the IVW method (OR: 0.906, 95% CI: 0.867-0.947). MR Egger, weighted median, and MR PRESSO methods got similar results. No heterogeneity was detected by Cochran’s Q test, and no single SNP was driving the overall causal effect by leave-one-out analysis. Conclusion: Our study provides genetic support for a causal relationship between circulating selenium level and schizophrenia, decreased circulating selenium level was associated with an elevated risk of schizophrenia.